Mulch and irrigation effects on plant-water relations and performance of cassava and sweet potato - Ghuman, B.S.; Lal, R. (Elsevier, 1983)
Mulch and irrigation effects on plant-water relations and performance of cassava cv. TMS 3001 and sweet potato cvs. TIS 2148 and TIS 2295 were investigated at Ibadan, Nigeria. Straw mulch @ 6 t/ha was spread immediately after planting of crops in September 1980. Irrigation equal to pan evaporation was applied during the dry season of 1980/81. Unmulched and/or nonirrigated plants of both crops had lower leaf water potential than mulched and/or irrigated. Averaged over all the treatments and cultivars, cassava had 15.00 h leaf water potential of −3.6 bars as compared to −9.6 bars of sweet potato. The daytime leaf diffusion resistance of cassava was similar (2–5 s cm−1) in unirrigated mulched and irrigated mulched and unmulched plots. But in unirrigated unmulched plots, the resistance increased to 19 s cm−1 at 15.00 h. Mulching did not affect leaf diffusion resistance (2–8 s cm−1) of both cultivars of sweet potato in irrigated plots. But in nonirrigated plots, leaf resistance increased with time during the day; the increase was less in mulched (from 2 to 40 s cm−1 in TIS 2148 and 3 to 13 s cm−1 in TIS 2295) than in unmulched (from 3 to 54 s cm−1 in TIS 2148 and 2 to 20 s cm−1 in TIS 2295) treatments. At harvest, the yields of cassava and sweet potato were not significantly affected by mulching. However, cassava yield was significantly greater in irrigated (24.7 t/ha) than in nonirrigated plots (18.2 t/ha). Similarly, irrigated sweet potato (at 8.5 t/ha of TIS 2148 and 8.7 t/ha of TIS 2295) outyielded the nonirrigated (at 5 t/ha of TIS 2148 and 2.8 t/ha of TIS 2295) one.